THE EFFECT OF PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON TRUST AND INTENTION TO OWN A BNI CREDIT CARD IN PEKANBARU CITY - Arrita, Rini; Zulkarnain; Garnasih, Raden Lestari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of Perceived Ease of Use, Perceived Usefulness, and Trust on the intention to own a BNI credit card in Pekanbaru City. The background of this study is based on the declining trend in the number of applications and approval rates for BNI credit cards from 2020 to 2024, amidst intense competition from other digital financial products such as e-wallets and Buy Now Pay Later (BNPL). This research methodology uses a quantitative approach with an AMOS-based Structural Equation Modeling (SEM) model, which integrates the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), and Trust theory. Data were obtained through questionnaires distributed to the target population. The results show that Perceived Ease of Use and Perceived Usefulness significantly and positively influence the intention to own a BNI credit card. However, the key finding of this study is the strong mediating role of the Trust variable. This means that even though potential customers experience the convenience and benefits of credit card products, their decision to purchase one depends heavily on their level of trust in Bank BNI. Factors such as information transparency, data security, and process clarity are crucial in building and maintaining this trust.